Antioxidant Role of Caralluma indica Stem Extract in Isoproterenol Induced Oxidative Stress in Albino Rats - Vadivu, R. Shunmuga; Velavan , S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Plants are important for human life on earth and serve as the food. Another important aspect of the plant is therapeutic use. Medicinal plants afford a best source of active compounds to find new medicines that have no adverse effects, such as those that are a very respectable source of disease treatment, that are associated with oxidative stress. Oxidative stress plays a significant role in the pathogenesis of a myocardial infarction (MI) and has been well recognized in the properties of isoproteinol-induced MI. Current research aims to investigate the role of antioxidants in the Caralluma indica stem extract (CISE) in isoproterenol -induced oxidative stress in albino rats. Depending on the results achieved, CISE can be a suitable candidate to reduce the oxidative stress induced by isoproterenol. CISE management shows an increase in antioxidant status in the treatment of isoproterenol as follows. The cardioprotective properties of CISE can be attributed to the antioxidant components of CISE. Graphical abstract of antioxidant role of Caralluma indica stem extract